Inhibition of ruminal urease - B.E. Brent; A. Adepoju; F. Portela; D. Richardson (Kansas Agricultural Experiment Station Research Reports, 1968)
Rumen bacteria elaborate an enzyme, urease. Urease is capable of breaking down urea to ammonia and carbon dioxide. Rumen bacteria then incorporate the ammonia into new amino acids and bacterial protein. Thus, urea can be used as a non-nitrogen source for ruminants. Unfortunately, urease often makes ammonia available faster than it can be used by rumen bacteria. That leads to poor utilization of urea or, in extreme cases, to toxicity.
Keywords: Cattlemen' s Day; 1968; Report of progress (Kansas State University. Agricultural Experiment Station); 518; Beef; Rumen; Urease; Bacterial cells